Effects of Topical Administration of Nimodipine on Cerebral Blood Flow following Subarachnoid Hemorrhage in Pigs - Wang, Fei (Mary Ann Liebert, Inc., 2013)
We sought to explore whether topical administration of nimodipine improves the abnormal cerebral perfusion following subarachnoid hemorrhage (SAH) in pigs. Fourteen pigs were randomly divided into three groups: sham (n=4), SAH (n=5), or SAH + nimodipine (n=5). The SAH model was established by injecting fresh autologous nonheparinized arterial blood into the suprasellae cistern. Nimodipine or saline placebo (0.04 g/mL) were administered to the operative area on the fourth day after the SAH model was established. The cerebral blood flow (CBF) was measured 60 min after topical administration of nimodipine by cranial SPECT/CT scans with 5 mCi 99mTc-ECD injected intravenously. The CCR (corticocebellar ratio) was calculated by dividing the counts/voxel of the whole cerebral hemisphere by the average count/voxel in the cerebellar region of reference and RD (relative dispersion). A predictor for impaired autoregulation of CBF was calculated by dividing standard deviation (SD) of regional perfusion by mean perfusion (RD=SD/Mean). CCR and RD were applied to describe hemisphere CBF and perfusion heterogeneity. Cerebral perfusion significantly decreased in the SAH group (CCR: 1.382±0.192, RD: 0.417±0.015) compared to sham (CCR: 1.988±0.346, RD 0.389±0.015) (p<0.05). Abnormal cerebral perfusion status, however, was not significantly improved in the nimodipine + SAH group (CCR: 1.503±0.107, RD: 0.425±0.018) compared to the SAH group (p>0.05). Topical administration of nimodipine did not significantly improve CBF following SAH. These findings were not consistent with our previous data demonstrating that the topical administration of nimodipine significantly alleviates cerebral vasospasm following SAH detected by TCD. Potential mechanisms governing these disparate outcomes require further investigation.